Regenerative Therapy Using Blood-Derived Stem Cells - Allan, David S.; Strunk, Dirk (Stem Cell Biology and Regenerative Medicine, 2012)
Regenerative medicine is the emerging science of how we can support our body to repair itself and encompasses innovative strategies to facilitate recovery after organ injury. Several types of blood-derived stem cells can be easily procured and have the potential to facilitate this repair process. Our understanding of the various cell types and precise mechanisms of repair are evolving quickly. In this book, several key types of blood-derived stem cells that participate in the repair of organ damage are reviewed and specific examples of how stem cells may improve heart damage and neurological injury are addressed. Practical approaches to preparing cellular products and regulatory issues that will govern translational studies in patients are also covered. Regenerative Therapy Using Blood-Derived Stem Cells is a timely publication of a fast-moving field that will stimulate further research and enquiry into the promising field of regenerative medicine.